Hydrophilic paclitaxel compound and preparation method thereof - LU XIULIAN; LI XU (2017)
The invention belongs to the technical field of medicine preparation, and particularly relates to a hydrophilic paclitaxel compound and a preparation method thereof. The preparation method of the hydrophilic paclitaxel compound comprises the following specific steps of reacting paclitaxel and a hydrophilic small molecule compound under catalysis of a basic catalyst to obtain a hydrophilic paclitaxel compound precursor; and then removing a protective group to obtain the final product hydrophilic paclitaxel compound. Compared with the prior art, the preparation method of the hydrophilic paclitaxel compound has the advantages of being simple, fast and high in yield; and after paclitaxel is modified by using the method structure, the chemical property is stable and the water solubility is greatly improved. 本发明属于药物制备技术领域，具体来说，涉及到种亲水性紫杉醇类化合物及其制备方法。所述亲水性紫杉醇类化合物的制备方法步骤具体如下：将紫杉醇与亲水性小分子化合物在碱性催化剂催化下反应得到亲水性紫杉醇化合物前体，然后脱去保护性基团得到最终产物亲水性紫杉醇化合物。与现有技术相比，本发明所述的亲水性紫杉醇类化合物制备方法具有简便、快速、收率高等优点；紫杉醇经此方法结构修饰后，化学性质稳定，水溶性有很大的提高。